Barakah Beats - Siddiqui, Maleeha (Scholastic Inc., 2022)
Nimra Sharif believes she has to hide her true self when attending public middle school for the first time, especially when wearing her hijab in school makes her friend, Jenna, seem to give her the cold shoulder when they are by their classmates. Desperate to fit in and surprised by the offer, Nimra joins the Barakah Beats, a music group formed by popular eighth-grade boys, hoping to gain some popularity for herself and win Jenna's friendship back. But, there is a catch--music is forbidden in her Islamic family, and Nimra must stay with the band only long enough to impress Jenna, but quit soon enough that her parents do not find out.